ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESELAMATAN DAN KECELAKAAN KERJA PADA KARYAWAN DAN PENGEMUDI - Shakinah Mawaddah; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Occupational safety is making working conditions safe by being equipped with safety equipment, good lighting, keeping floors and stairs free from water, oil, mosquitoes, and maintaining good water facilities Smith and Sonesh in Priatna and Andika (2018). This type of research The method of data collection is a literature review study to find empirical studies published in journals since 2018. The purpose of this literature review is to find out the research results and thoughts that have been produced by previous researchers. The conclusion is that accidents often occur due to humans who are not careful both when driving and working, as we know many employees and drivers are injured and even die. It’s all caused by humans who are less careful in doing something